2010
DOI: 10.1038/pj.2010.101
|View full text |Cite
|
Sign up to set email alerts
|

Naphthalene-based oligothiophene-stacked polymers

Abstract: We report the synthesis and properties of p-stacked polymers consisting of oligothiophene and naphthalene as the stacked p-system and the scaffold, respectively. The titled polymers were obtained by the Suzuki-Miyaura coupling reaction. Oligothiophene units were layered in proximity, B3.0 Å from each other. Contribution of the quinoidal structure of the oligothiophene units involving the naphthalene scaffolds in the excited state resulted in relatively high photoluminescence quantum efficiencies. The polymers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 77 publications
1
11
0
Order By: Relevance
“…[26][27][28][29][30] We have recently reported the synthesis of polymers with layered aromatic rings using a xanthene scaffold as a hairpin-shaped linker; these polymers exhibit intramolecular π-stacked structures with multiple aromatic rings stacked along a single polymer chain. [31][32][33][34][35][36] They can be regarded as the assembly of several small π-conjugated units. However, owing to the small size of the π-conjugated moieties and to the bulkiness of the xanthene scaffold, their intermolecular interactions were relatively weak.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29][30] We have recently reported the synthesis of polymers with layered aromatic rings using a xanthene scaffold as a hairpin-shaped linker; these polymers exhibit intramolecular π-stacked structures with multiple aromatic rings stacked along a single polymer chain. [31][32][33][34][35][36] They can be regarded as the assembly of several small π-conjugated units. However, owing to the small size of the π-conjugated moieties and to the bulkiness of the xanthene scaffold, their intermolecular interactions were relatively weak.…”
Section: Introductionmentioning
confidence: 99%
“…Their thermo­responsive optical behavior has been illustrated previously, which highlights the importance of this kind of materials for different optoelectronic and multi‐responsive devices . The electro‐chemiluminescence properties of oligothiophene‐based nano­structures have been reported by Bard et al Furthermore, a few other reports have demonstrated the optical and electronic properties of oligothiophene nanomaterials . Diegelmann et al have discussed the possible applications of an oligothiophene‐based supramolecular nanostructure in both biological and optoelectronic devices based on their prominent photophysical change upon aggregation .…”
Section: Introductionmentioning
confidence: 88%
“…[30][31][32] The electro-chemiluminescence properties of oligothiophene-based nano structures have been reported by Bard et al [ 33 ] Furthermore, a few other reports have demonstrated the optical and electronic properties of oligothiophene nanomaterials. [34][35][36] Diegelmann et al have discussed the possible applications of an oligothiophene-based supramolecular nanostructure in both biological and optoelectronic devices based on their prominent photophysical change upon aggregation. [ 37 ] The possible applications of oligothiophene-based nanomaterials in high-performance photovoltaic devices has also been demonstrated by Chen and coworkers.…”
Section: Introductionmentioning
confidence: 99%
“…Aromatic molecules are among the most important classes of the compounds having a crucial role in biochemistry and material chemistry (Morisaki et al, 2010). It is well known that the relative orientation and distance between the aromatic rings in the solid state affects the electronic delocalization and therefore important bulk properties.…”
Section: Introductionmentioning
confidence: 99%